High heterogeneity on the accepted vaccines for COVID-19 certificates in European countries. Issue 48 (July 2022) - Dal-Ré, Rafael; Banzi, Rita; Becker, Sören L.; Launay, Odile; Pavli, Androula
Abstract: Background: We aimed to elucidate which vaccines were accepted by European countries as valid proof of vaccination against COVID-19 for international travelers. Method: On 27-September-2021 a cross-sectional study was conducted on VisaGuide.World, that reports on valid vaccines for international travelers. Other databases, lay press and regulatory agencies were also checked. The main outcome measure was which of the vaccines included on the WHO emergency use listing (EUL) [ChAdOx1 (Vaxzevria, Covishield), BNT162b2, mRNA-1273, Ad26.CoV2.S, BBIBP-CorV, CoronaVac] and Sputnik V, were accepted in each country. The influence of the vaccines approved for COVID-19 vaccination programs on the vaccines recognized as proof of vaccination was assessed. Results: There was a remarkable heterogeneity on the vaccines accepted as proof of vaccination among 46 countries. Russia accepted only one. Cyprus, Greece and Slovenia accepted all vaccines considered. Eleven countries accepted the seven WHO EUL vaccines: eight EU countries, plus Iceland, Norway and Switzerland. Seven EU countries accepted only the four EMA-authorized vaccines. Considering Covishield as equivalent to Vaxzevria, 69% of countries recognized only vaccinated travelers who received any of the vaccines approved for vaccination programs in the country of arrival as valid. Conclusion: Vaccines accepted as proof of vaccination should be harmonized. Accepting any of the WHO EUL vaccines would be a scientifically sound objective.